ERROR ANALYSIS ON EFL STUDENTS’ INDEPENDENT WRITING TASK OF TOEFL iBT - Nurhayati S.; Rahmi Aulia Nurdini (UIN Alauddin Makassar, 2019)
TOEFL iBT, introduced in 2005, is a standardized test measuring English proficiency for not only university students where English is the language of instructions but also a requirement of many employers (Gallagher, 2016). Four skills tested in TOEFL iBT are : Reading, Listening, Speaking and Writing. The writing part is the object of this study focusing on analyzing EFL students’ essay writing errors. Essay is one type of writing tasks which is called as independent writing. The researchers analyzed some samples of independent writing task of 7 TOEFL iBT candidates. Examining 16 writing tasks entirely, the researchers categorized the errors into three major categories: grammar, mechanics, and content errors. This study found that most frequent grammatical errors were in agreement (30,5%), verb (18%), and followed by sentence structure (16,3%). The mechanic errors are in the uses of capitalization which is mostly in the letter of ‘i’ as a first singular pronoun and punctuation errors containing the omission and incorrect use of comma. The last finding is about content errors comprising plagiarism of using the phrases or sentences from the question; question addressing where the essays did not address the topic of the task well; and the missing of conlusion part which is obligatory in essay structure. The findings of this study are expected to enhance TOEFL iBT teachers’ understanding of candidates’ problems and to improve TOEFL iBT preparatory materials for having more effective teaching approach. Keywords: Error Analysis, TOEFL iBT writing, Independent writing task ABSTRAKTOEFL iBT, diperkenalkan pada tahun 2005, adalah tes standar yang mengukur kemahiran bahasa Inggris tidak hanya mahasiswa di mana bahasa Inggris adalah bahasa instruksi tetapi juga persyaratan dalam pekerjaan (Gallagher, 2016). Empat keterampilan yang diuji dalam TOEFL iBT adalah: Membaca, Mendengarkan, Berbicara dan Menulis. Kemampuan menulis adalah objek penelitian ini yang berfokus pada analisis kesalahan penulisan esai pada siswa yang mempelajari bahasa Inggris sebagai bahasa asing. Esai adalah salah satu jenis tugas penulisan yang disebut penulisan independen. Para peneliti menganalisis beberapa sampel tugas penulisan esai dari 7 kandidat TOEFL iBT. Para peneliti menganalisis 16 esai dengan mengelompokkan kesalahan menjadi tiga kategori utama: tata bahasa, mekanika, dan kesalahan konten. Penelitian ini menemukan bahwa kesalahan tata bahasa yang paling sering adalah dalam agreement (30,5%), kata kerja (18%), dan diikuti oleh struktur kalimat (16,3%). Kesalahan mekanik dalam penggunaan huruf besar yang sebagian besar dalam huruf 'i' sebagai kata ganti tunggal pertama dan kesalahan tanda baca pada penggunaan koma. Penemuan terakhir adalah tentang kesalahan konten yang terdiri dari plagiarisme dari menggunakan frasa atau kalimat dari pertanyaan; kesalahpahaman atas pertanyaan di mana esai tidak menjawab pertanyaan dengan baik; dan hilangnya bagian kesimpulan yang wajib dalam struktur esai. Temuan penelitian ini diharapkan dapat meningkatkan pemahaman guru tentang kendala-kendala yang dihadapi pembelajar TOEFL iBT dan untuk meningkatkan persiapan guru dalam mengajar TOEFL iBT untuk mendapatkan pengajaran yang lebih efektif. Kata kunci: Analisis Kesalahan, Kemampuan Menulis dalam TOEFL iBT, tugas penulisan